2014
DOI: 10.1177/000313481408000332
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Perforated Appendicitis in Children: Focus on Phlegmon

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The general characteristics of the included studies are shown in Table 1. Designs of the studies were one pilot randomized controlled trial [6], two non-randomized prospective studies [5,18], and 11 retrospective studies [12,13,[15][16][17][18][19][20][21][22][23]. These 14 studies included 1355 children, of which 333 were included in the EA group with a median [range] of 19 patients per study and 1022 in the NOT group with a median [range] of 32 patients per study.…”
Section: Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The general characteristics of the included studies are shown in Table 1. Designs of the studies were one pilot randomized controlled trial [6], two non-randomized prospective studies [5,18], and 11 retrospective studies [12,13,[15][16][17][18][19][20][21][22][23]. These 14 studies included 1355 children, of which 333 were included in the EA group with a median [range] of 19 patients per study and 1022 in the NOT group with a median [range] of 32 patients per study.…”
Section: Included Studiesmentioning
confidence: 99%
“…The interrater reliability for judging the subdomains of the ROBINS-I and Risk of Bias tool 2.0 was substantial (76% agreement). All studies were assessed as moderate to serious risk of bias on the primary outcome (overall complication rate) according to the ROBINS-I tool and some concerns were expressed according to the Risk of Bias tool 2.0 for the study by St Peter (Table 2) [5,6,[12][13][14][15][16][17][18][19][20][21][22][23]. Bias due to confounding was serious in most cohort studies and moderate in only 4 of them [5,13,18,21].…”
Section: Quality Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations